Sharia Bank Practice in Indonesia: Theory and Practice - alif, jeffits; Azatil Isma, Aam; Yope, Sri Aisyah; Fitrawansyah; Harviani, Evi (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Abstract The 1998 monetary crisis that hit Indonesia encouraged people to look for other economic alternatives, namely the sharia economy. However, the practice of Islamic economics in Indonesia is still thick with conventional economic practices, especially those found in Islamic financial institutions or Islamic banking. This study uses a qualitative research method to examine the literature to examine how the practice of Islamic economics in Islamic banking in Indonesia. The results show that the practice of sharia sharia economics, namely murabahah, the application of fines, and the use of contracts in Islamic banks in Indonesia is still far from the principles of Islamic law, and is supported by sharia economic regulators who misinterpret the implementation of sharia economics. Keywords: Sharia Bank, Islamic Economy, Conventional Bank